TIPOLOGI METODE IJTIHAD FIKIH KONTEMPORER - Basri Na'ali (Alhurriyah, 2016)
This paper attempts to review the typology of the approach taken by the contemporary jurists in determining the law against new problems encountered in the community. Typology method of Contemporary Fiqh ijtihad is a method for understanding the growing Islamic law in the nowaday context , and in the dynamics and dialectics understanding context which are strongly associated with the dimensions of space and time. Every jurist has its own perspective in understanding the law passages. From the results of the study, authors concluded that the typology method of ijtihad Jurisprudence used by contemporary jurists can be categorized into seven forms, mazhabi, Intiqa’i, insya'i, Intiqa’i ainsya ' i, istishlahi, Zahiri and taswighi